Potensi Wisata Kabupaten Indramayu - Wahyu Iryana (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2020)
Indramayu is an area that has a very rich tourism potential, this is the basic capital of tourism in Indramayu long term. But the main point at issue is how the potential is prospective and actual. Prospective step and actualization is of course a management problem. Therefore, tourism management is an absolute requirement for the development of tourism activities. One concrete form of tourism management is promotion or advertising. Professionalism in doing real work is part of the struggle.